The application of classic laryngeal mask airway combined with a self-created adaptor in interventional bronchoscopy for pediatric patients: A case series and literature review - Song, Xuesong; Yan, Na; Zhao, Zhuang; Li, Zhiwen (Frontiers in Anesthesiology, 2022)
Purpose: To verify the feasibility of classic laryngeal mask airways combined with self-created adaptors in the interventional bronchoscopy of subglottic lesions for pediatric patients. Methods: Three children who were diagnosed with upper airway lesions, subglottic stenosis (scar hyperplasia) and congenital laryngomalacia were respectively subjected to fiberoptic bronchoscopy (FOB) and therapeutic interventions. A classic laryngeal mask airway combined with a self-created adaptor was applied during the FOB procedures. Results In our cases, the vocal cord, glottis, trachea and lesions were easily exposed, other than an effective ventilation or oxygenation for the patients. Furthermore, both surgeons and patients were comfortable with the technique. Vital signs were stable during the procedures, including blood pressure, heart rate and the saturation of pulse oximetry. Conclusion By retaining spontaneous breathing, the application of a classic laryngeal mask airway combined with a self-created adaptor is a considerable alternative method of airway management during FOB interventional procedures for pediatric patients.